(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2025)
The study investigated the influence of artificial intelligence systems on quality of teaching and learning in public universities in Anambra State. Two research questions guided the study and two hypotheses were tested at 0.05 level of significance. The correlational research design was used for the study. The population of the study comprised 74 lecturers of the Department of Educational Management and Policy or Department of Educational Foundations from two public universities in Anambra State. The instrument for data collection was a validated questionnaire. The instrument was pilot tested and the application of Statistical Package for Social Sciences (SPSS) version 21 using Cronbach Alpha reliability method on the data obtained yielded reliability co-efficient value of 0.87 for cluster A and 0.77 for cluster B with an overall coefficient value of 0.82 for QAI and 0.85 for QTLUQ. Pearson Product Moment Correlation analysis was used to analyse data for the study. The findings of the study revealed that intelligent tutoring systems and smart classroom technology have a very high positive relationship on the quality of teaching and learning in public universities in Anambra State. Finding of the study further revealed intelligent tutoring systems and smart classroom technology have a significant influence on the quality of teaching and learning in public universities in Anambra State. Based on these findings, the researchers recommended among others that administrators of public universities should collaborate with private organizations in the area of funding, provision of digital infrastructure and technical support for successful integration of intelligent tutoring systems and smart classroom technologies for teaching and learning.